(untitled) (Alijtihed Journal on Legal and Economic Studies, 2023)
Refugee protection guarantees represent those rules that guarantee protection for his rights and freedoms during the international armed conflict. Within the framework of the subject of the research,two international laws frame both of these protections. Namely international humanitarian law and international refugee law. So we have two measures, the first is the integration scale between international law and the second in the scale of continuity in the succession of the application of international law in time.